Estimation and Analysis of the Cost Function of the Food Industries in Iraq - QASIM, Mustafa; Al-Birmani , Salah (Journal of Economics and Administrative Sciences, 2025)
The paper analyses the production costs of Iraq's food industry and tries to establish its optimum production level. Declining contribution to GDP resulting from high production costs, competition brought about by imported products, and economic instability has been showed by the study in focusing on the industry. The paper employs econometric analysis through EViews-10 to estimate cost functions across different industrial scales (Small, Medium, and Large) for the period between the years 2004 and 2022. Findings reveal that the optimal production efficiency has not been attained so far for the food industry of Iraq. It is suffering from a high dependency on imported raw materials which increases cost and lowers their competitiveness. The production cost analysis has proven that production costs follow a cubic function indicating that food industries are still in the early phases of production, meaning there are high cost inefficiencies. In other words, the estimated value of cost elasticity (0.819) indicates that the production level can be increased to yield higher profits.It advocates for cost minimization and productivity improvement as ways of attaining economic efficiency. It presents features that will strengthen agriculture-industry linkages towards reduced reliance on imports. The paper will therefore inform policy decisions and economic models toward making Iraq's food industry sustainable and competitive.